Population description and clinical response assessment for spinal metastases: part 2 of the SPIne response assessment in Neuro-Oncology (SPINO) group report. Issue 9 (24th March 2018) - Laufer, Ilya; Lo, Simon S; Chang, Eric L; Sheehan, Jason; Guckenberger, Matthias; Sohn, Moon-Jun; Ryu, Samuel; Foote, Matthew; Muacevic, Alexander; Soltys, Scott G; Chao, Samuel; Myrehaug, Sten; et al.
Abstract: Background: Approximately 40% of metastatic cancer patients will develop spinal metastases. The current report provides recommendations for standardization of metrics used for spinal oncology patient population description and outcome assessment beyond local control endpoints on behalf of the SPIne response assessment in Neuro-Oncology (SPINO) group. Methods: The SPINO group survey was conducted in order to determine the preferences for utilization of clinician-based and patient-reported outcome measures for description of patients with spinal metastases. Subsequently, ClinicalTrials.gov registry was searched for spinal oncology clinical trials, and measures for patient description and outcome reporting were identified for each trial. These two searches were used to identify currently used descriptors and instruments. A literature search was performed focusing on the measures identified in the survey and clinical trial search in order to assess their validity in the metastatic spinal tumor patient population. References for this manuscript were identified through PubMed and Medline searches. Results: Published literature, expert survey, and ongoing clinical trials were used to synthesize recommendations for instruments for reporting of spinal stability, epidural tumor extension, neurological and functional status, and symptom severity. Conclusions: Accurate description of patient population and therapy effects requires a combination of clinician-based and patient-reported outcome measures. The current report provides international consensus recommendations for the systematic reporting of patient- and clinician-reported measures required to develop trials applicable to surgery for spinal metastases and postoperative spine stereotactic body radiotherapy (SBRT).